PENGARUH PELAYANAN FISKUS DAN SANKSI DENDA TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN - Mullery, Azril Febrian; Tanjung, Hendra (LPPM Universitas Bina Bangsa, 2024)
This study aims to determine the effect of the service of tax authorities and Tax Sanctions on Taxpayer Compliance in Paying Earth and Building Taxes. The research method used is quantitative with primary data as the data source. The population of this study consisted of taxpayers registered at the Sukabumi City Regional Revenue Management UPTD office, with a sample of 100 respondents selected using the Convenience Sampling method. The results showed that the service of tax authorities had a partial effect on Taxpayer Compliance in Paying Earth and Building Tax, because the tcount> ttable value was 21.746> 1.661. Tax Sanctions also partially affect taxpayer compliance in paying land and building tax, with a tcount> ttable value of 6.252> 1.661. Simultaneously, the service of tax authorities and tax Sanctions have a significant effect on taxpayer compliance in paying Earth and building tax, with a value of Fcount> Ftable, namely 108.518> 3.089. Therefore, it can be concluded that the service of tax authorities and tax Sanctions simultaneously have a significant effect on Taxpayer Compliance in Paying Earth and Building Taxes